Bacillus thuringiensis DB27 Produces Two Novel Protoxins, Cry21Fa1 and Cry21Ha1, Which Act Synergistically against Nematodes - Iatsenko, Igor (American Society for Microbiology, 2014)
Bacillus thuringiensis has been widely used as a biopesticide, primarily for the control of insect pests, but some B. thuringiensis strains specifically target nematodes. However, nematicidal virulence factors of B. thuringiensis are poorly investigated. Here, we describe virulence factors of nematicidal B. thuringiensis DB27 using Caenorhabditis elegans as a model. We show that B. thuringiensis DB27 kills a number of free-living and animal-parasitic nematodes via intestinal damage. Its virulence factors are plasmid-encoded Cry protoxins, since plasmid-cured derivatives do not produce Cry proteins and are not toxic to nematodes. Whole-genome sequencing of B. thuringiensis DB27 revealed multiple potential nematicidal factors, including several Cry-like proteins encoded by different plasmids. Two of these proteins appear to be novel and show high similarity to Cry21Ba1. Named Cry21Fa1 and Cry21Ha1, they were expressed in Escherichia coli and fed to C. elegans, resulting in intoxication, intestinal damage, and death of nematodes. Interestingly, the effects of the two protoxins on C. elegans are synergistic (synergism factor, 1.8 to 2.5). Using purified proteins, we determined the 50% lethal concentrations (LC(50)s) for Cry21Fa1 and Cry21Ha1 to be 13.6 μg/ml and 23.9 μg/ml, respectively, which are comparable to the LC(50) of nematicidal Cry5B. Finally, we found that signaling pathways which protect C. elegans against Cry5B toxin are also required for protection against Cry21Fa1. Thus, B. thuringiensis DB27 produces novel nematicidal protoxins Cry21Fa1 and Cry21Ha1 with synergistic action, which highlights the importance of naturally isolated strains as a source of novel toxins.